An Economic Evaluation of Maize–Mustard Cropping System in Response to the Complementary Influence of Organic and Inorganic Source of Nutrients - Rao, P. M.; Sagar, G. E. C. H. Vidya; Suresh, K.; Padmaja, G.; Reddy, S. Narender (International Journal of Economic Plants, 2026)
A field experiment was conducted during kharif, 2018 and 2019 and rabi 2018–19 and 2019–20 at the Regional Agricultural Research Station, Polasa, Jagtial, to evaluate the effect of integrated nutrient management (INM) practices on yield attributes, yield, and economics of maize in a maize–mustard cropping system. The experiment on maize during kharif was laid out in a randomized block design with nine treatments and three replications. The treatments included N₁: 100% recommended dose of fertilizers (RDF);N₂:75% recommended dose of nitrogen (RDN)+25% N through farmyard manure (FYM); N₃:75% RDN+25% N through vermicompost; N₄: 75% RDN+25% N through poultry manure; N₅: 75% RDN+25% N through sheep manure; N₆: 75% RDN+25% N through neem cake; N₇: 75% RDN+Azotobacter at 5 kg ha-1; N₈: 75% RDN+Azospirillum at 5 kg ha-1; and N₉: 75% RDN+Azotobacter at 2.5 kg ha-1+Azospirillum at 2.5 kg ha-1. Each main plot was further subdivided into four subplots during the rabi season to accommodate mustard treatments under a split-plot arrangement. The fertilizer treatments imposed on mustard included F₁: 0:0:0 kg ha-1 N:P:K (control); F₂: 30:20:20 kg ha-1 NPK (50% RDF); F₃: 45:30:30 kg ha-1 NPK (75% RDF); and F₄: 60:40:40 kg ha-1 NPK (100% RDF). Recommended agronomic practices were followed for both crops throughout the experiment. The study evaluated the effect of organic, inorganic, and biofertilizer sources on productivity and profitability of the maize–mustard system. Economic parameters including gross returns, net returns, and benefit–cost ratio were calculated to assess feasibility of nutrient management practices. The findings highlighted sustainable nutrient management strategies for improving maize-based cropping systems.